Substantial rearrangements, single nucleotide frameshift deletion and low diversity in mitogenome of Wolbachia-infected strepsipteran endoparasitoid in comparison to its tephritid hosts - Sharon Towett-Kirui; Jennifer L. Morrow; Markus Riegler (Scientific Reports, 2022)
Abstract Insect mitogenome organisation is highly conserved, yet, some insects, especially with parasitic life cycles, have rearranged mitogenomes. Furthermore, intraspecific mitochondrial diversity can be reduced by fitness-affecting bacterial endosymbionts like Wolbachia due to their maternal coinheritance with mitochondria. We have sequenced mitogenomes of the Wolbachia-infected endoparasitoid Dipterophagus daci (Strepsiptera: Halictophagidae) and four of its 22 known tephritid fruit fly host species using total genomic extracts of parasitised flies collected across > 700 km in Australia. This halictophagid mitogenome revealed extensive rearrangements relative to the four fly mitogenomes which exhibited the ancestral insect mitogenome pattern. Compared to the only four available other strepsipteran mitogenomes, the D. daci mitogenome had additional transpositions of one rRNA and two tRNA genes, and a single nucleotide frameshift deletion in nad5 requiring translational frameshifting or, alternatively, resulting in a large protein truncation. Dipterophagus daci displays an almost completely endoparasitic life cycle when compared to Strepsiptera that have maintained the ancestral state of free-living adults. Our results support the hypothesis that the transition to extreme endoparasitism evolved together with increased levels of mitogenome changes. Furthermore, intraspecific mitogenome diversity was substantially smaller in D. daci than the parasitised flies suggesting Wolbachia reduced mitochondrial diversity because of a role in D. daci fitness.